Fresh frozen plasma as a source of plasminogen for ligneous conjunctivitis: Case report and a review of the literature - Benjamin J Park; David Camoriano; Mark C Vital; Patricia Chévez-Barrios; John D Goosey; Marcel Belloso (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2021)
Purpose: To describe management of a patient with ligneous conjunctivitis secondary to plasminogen deficiency and review the literature on treatment with plasminogen. Design: Interventional case report. Methods: A 6-year-old Caucasian girl developed ligneous conjunctivitis recalcitrant to debridement and treatment with topical cyclosporin A and steroids. The literature was reviewed regarding treatment of ligneous conjunctivitis with plasminogen. Results: The patient was treated with plasminogen containing drops derived from her father's fresh frozen plasma. The ligneous conjunctivitis resolved, and the patient was managed on these drops for the following 8 years, initiating treatment for flares and tapering according to clinical response. Conclusions: Plasminogen drops concentrated from fresh frozen plasma are a safe and effective option for long-term treatment of ligneous conjunctivitis.